2016
DOI: 10.1016/j.virol.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the dimerization and substrate recognition specificity of porcine epidemic diarrhea virus 3C-like protease

Abstract: Porcine epidemic diarrhea virus (PEDV), a member of the genus Alphacoronavirus, has caused significant damage to the Asian and American pork industries. Coronavirus 3C-like protease (3CL(pro)), which is involved in the processing of viral polyproteins for viral replication, is an appealing antiviral drug target. Here, we present the crystal structures of PEDV 3CL(pro) and a molecular complex between an inactive PEDV 3CL(pro) variant C144A bound to a peptide substrate. Structural characterization, mutagenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 51 publications
3
81
0
Order By: Relevance
“…5A and B). Otherwise, previous studies have shown that the substrate-binding sites and active sites of the 3CLSP and 3CL protease are located between domains I and II in their structures (Tian et al, 2009;Ye et al, 2016). The amino acid residue His39 in 3CLSP (corresponding to His41 of 3CL protease) plays a vital role in substrate combination and catalysis.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…5A and B). Otherwise, previous studies have shown that the substrate-binding sites and active sites of the 3CLSP and 3CL protease are located between domains I and II in their structures (Tian et al, 2009;Ye et al, 2016). The amino acid residue His39 in 3CLSP (corresponding to His41 of 3CL protease) plays a vital role in substrate combination and catalysis.…”
Section: Discussionmentioning
confidence: 98%
“…In the 3CLSP and Y. Shi et al Veterinary Microbiology 213 (2018) 114-122 3CL protease, the S1 specificity pocket is essential for recognition of the side chain of the substrate P1 residue and determination of the enzyme's preference (Tian et al, 2009;Ye et al, 2016). Hence, the residues of S1 specificity pockets were selected as targets for molecule docking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations